2019
DOI: 10.1089/wound.2018.0901
|View full text |Cite
|
Sign up to set email alerts
|

An Equine Wound Model to Study Effects of Bacterial Aggregates on Wound Healing

Abstract: Objective: Relevant animal models to study effects of bacterial aggregates on wound healing are lacking. We aimed at establishing an equine wound model with bacterial aggregates to investigate the impact of bacterial inoculation on normal (thorax) and impaired (limb) wound healing. Approach: Wounds were created on three limbs and both thorax sides of six horses. Twelve out of 20 wounds per horse were inoculated with 10 4 Staphylococcus aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 49 publications
(74 reference statements)
4
23
0
Order By: Relevance
“…We have recently shown in an equine experimental wound model that biofilms were present in equine limb wounds but not in body wounds [17]. Further, in a recent equine experimental wound model with bacterial inoculation, we found biofilms to negatively affect wound healing of distal limb wounds but not body wounds [18]. Based on these initial findings of biofilms in equine limb wounds and on several similarities between equine and human impaired wound healing [19][20][21], there is a good reason to expect biofilm formation to also play a role in the delayed healing of limb wounds in horses.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…We have recently shown in an equine experimental wound model that biofilms were present in equine limb wounds but not in body wounds [17]. Further, in a recent equine experimental wound model with bacterial inoculation, we found biofilms to negatively affect wound healing of distal limb wounds but not body wounds [18]. Based on these initial findings of biofilms in equine limb wounds and on several similarities between equine and human impaired wound healing [19][20][21], there is a good reason to expect biofilm formation to also play a role in the delayed healing of limb wounds in horses.…”
Section: Introductionmentioning
confidence: 76%
“…There is only a very sparse bulk of literature on biofilm-related infections and their diagnosis and management in veterinary clinical medicine [11][12][13][14][15][16][17][18][49][50][51]. To understand the subject, we currently have to broaden our view and look to other scientific areas (such as experimental medicine, biofilm research, and human clinical medicine).…”
Section: Biofilm In Generalmentioning
confidence: 99%
“…Pseudomonas aeruginosa (gram-negative) was chosen to demonstrate the specific mechanism of IA and its efficiency on both gram-positive and gram-negative bacteria. It is noteworthy that, both these species, are commonly associated with tissue infections [ 21 ]. The results showed that IA was able to completely suppress the bacterial growth on all the tested microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies were available from a study involving experimental excisional dermal wounds in six adult horses . Horses were clinically healthy and were without any signs or history of dermatological diseases or injuries.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure is described in detail elsewhere . In brief, the horses had four wounds (2 × 2 cm) created on the lateral aspect of the metatarsus/‐carpus (limb) and on the lateral thoracic wall (body).…”
Section: Methodsmentioning
confidence: 99%